Evidence-based interventions in primary care following acute coronary syndrome in Australia and New Zealand: a systematic scoping review. Issue 1 (December 2016) - Bhagwat, Manavi; Woods, John; Dronavalli, Mithilesh; Hamilton, Sandra; Thompson, Sandra
Abstract Background Coronary artery disease has a significant disease burden, but there are many known barriers to management of acute coronary syndrome (ACS). General practitioners (GPs) bear considerable responsibility for post-discharge management of ACS in Australia and New Zealand (NZ), but knowledge about the extent and efficacy of such management is limited. This systematic review summarises published evidence from Australia and New Zealand regarding management in primary care after discharge following ACS. Methods A search of PubMed, Scopus, CINAHL-Plus and PSYCINFO databases in August 2015 was supplemented by citation screening and hand-searching. Literature was selected based on specified criteria, and assessed for quality using the Mixed Methods Appraisal Tool (MMAT). Extracted data was related to evidence-based interventions specified by published guidelines. Results The search yielded 19 publications, most of which reported on quantitative and observational studies from Australia. The majority of studies scored at least 75 % on the MMAT. Diverse aspects of management by GPs are presented according to categories of evidence-based guidelines. Data suggests that GPs are more likely to prescribe ACS medications than to assist in lifestyle or psychological management. GP referral to cardiac rehabilitation varied, and one study showed an improvement in the number of ACS patients with documented ACS management plans. Few studies described successful interventions to improve GP management, though some quality improvement efforts through education and integration of care with hospitals were beneficial. Limited data was published about interventions effective in rural, minority, and Indigenous populations. Conclusions Research reflects room for improvement in GP post-discharge ACS management, but little is known about effective methods for improvement. Additional research, both observational and interventional, would assist GPs in improving the quality of post-discharge ACS care.